Intellectual production of the professors from Faculty of Education/UFRGS: analysis of documents typology - Ferreira, Ana Gabriela Clipes (Faculdade de Filosofia e Ciências, 2013)
This article aims to approach the intellectual production of the Professors from the Faculty of Education at the Universidade Federal do Rio Grande do Sul (FACED/UFRGS). This study is about a quantitative traits with qualitative analyzes using mixed methods. Through the Common Command Language (CCL) command at the software Aleph, it was collected the productions deposited from 2007 to 2010 and it was confronted with the data of the 2010 Census of Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq). The type of document on which the FACED departments publish more were the papers presented in annals of international events, followed by chapters of books and articles in national journals indexed. Concluded that although constrained, the method used enables the analysis of productivity of diversified documents, which would not be possible in a database collection.